(untitled) (International Journal of Environmental Sciences, 2025)
This study explores the moderating effect of religious faith intensity on Chinese tourists’ revisit intentions to Taoist sacred sites, specifically Qingcheng Mountain, within the context of ideological constraints limiting overt religious expression in China. Utilizing the Theory of Planned Behavior (TPB), the research examines how spiritual motivations (Pilgrimage to Holy Land, A) and perceived health wellness value (F) influence revisit intentions (E), mediated by attitude (B), subjective norms (C), and perceived behavioral control (D). A sequential explanatory mixed-methods design was employed, combining structural equation modeling (SEM) with qualitative interviews. Results indicate that religious faith intensity (R) significantly moderates the relationship between pilgrimage motivations and revisit intentions, with stronger effects among highly devout pilgrims. Less devout visitors prioritize health benefits through Taoist practices like Tai Chi and Qigong, reflecting a culturally acceptable channel for spiritual expression under ideological restrictions. The findings contribute to spiritual and wellness tourism literature, offering practical insights for sustainable Taoist tourism development.